THE MODEL OF EFFICIENCY MANAGEMENT OF TRANSACTION COSTS IN LEASING ORGANIZATIONS - L. Sh. Zainutdinova (Russian Journal of Economics and Law)
The article views the principles of transaction costs management and presents the sequence of managerial stages and transactional costs analysis. The author views the technique of economic efficiency evaluation of a leasing organization activity.